1999
DOI: 10.1007/s004290050242
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of peptide transporter PEPT2 mRNA in the rat nervous system

Abstract: The signaling action of neuropeptides in the brain is terminated by breakdown through extracellular peptidases and subsequent removal of the peptide fragments from the extracellular fluid via specific transporter proteins. Here we describe the anatomical distribution in the rat nervous system of the recently isolated high affinity peptide transporter PEPT2. Using nonisotopic in situ hybridization we demonstrate that PEPT2 mRNA is expressed in brain by astrocytes, subependymal cells, ependymal cells and epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 26 publications
(20 reference statements)
5
86
1
Order By: Relevance
“…Another high affinity peptide transporter, PEPT2, has been shown to be present in the central nervous system by Northern blot and in situ hybridization studies in mammals (9,14,15). The ectopic expression approach proves to be particularly useful for pinpointing the precise time and place of GFP expression because cell lineages can be simultaneously observed using differential interference contrast imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another high affinity peptide transporter, PEPT2, has been shown to be present in the central nervous system by Northern blot and in situ hybridization studies in mammals (9,14,15). The ectopic expression approach proves to be particularly useful for pinpointing the precise time and place of GFP expression because cell lineages can be simultaneously observed using differential interference contrast imaging.…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that OPT3 might play an important role in H ϩ homeostasis in C. elegans in addition to its likely role in the clearance of peptides arising from neuropeptide metabolism. In mammals, PEPT2 is expressed in the brain, and a similar role for this transporter in the clearance of peptide products arising from the hydrolysis of neuropeptides within the brain has been postulated (13)(14)(15)(16).…”
mentioning
confidence: 96%
“…More recently, PEPT2 has been identified in the peripheral nervous system, in the membranes and cytoplasm of satellite glial cells surrounding the ganglionic neurons (29), and in the central nervous system. In situ hybridization analysis revealed its presence in the brain in astrocytes, ependymal and subependymal cells, and in epithelial cells of the choroid plexus (8). In the lung, PEPT2 is expressed in type II pneumocytes and in the apical membrane of tracheal and bronchial epithelial cells (31).…”
Section: Tissue Distribution Of Pept1 and Pept2 And Their Tubular Locmentioning
confidence: 99%
“…It was initially cloned from a human kidney cDNA library (4) and is characterized as a high affinity (i.e., M K m values), low capacity transporter (5). PEPT2 mRNA transcripts (6,7), protein (8,9) and functional activity (10)(11)(12)(13)(14), along with PHT1 mRNA transcripts (15) have been described in the choroid plexus. Functional and immunocytochemical data in primary cultures of rat choroid plexus epithelial cells have demonstrated that PEPT2 is expressed on the apical plasma membrane (i.e., CSF-facing) and functions to clear di-and tripeptides from CSF (9).…”
Section: Introductionmentioning
confidence: 99%